ANALISIS KESALAHAN BERBAHASA DALAM TUGAS MAKALAH MAHASISWA PROGRAM STUDI PGMI SEMESTER III TAHUN AKADEMIK 2019/2020 - Rita; Laeli Qadrianti; Amran AR (Jurnal Pendidikan Dasar dan Keguruan, 2020)
This study aims to describe the form of language errors in the papers of the Madrasah Ibtidaiyah Teacher Education Study Program Odd Semester Academic Year 2019/2020. This research is a descriptive qualitative research. Data source is obtained from language errors in student paper assignments. Language errors analyzed include spelling mistakes. The data collection method used is the documentation method. The data that has been obtained is then analyzed using Miles and Huberman's theory which includes data reduction, display or presentation of data, then conclusions. Based on the results of this study found the form of language errors in the papers of PGMI Study Program Semester III Academic Year 2019/2020 namely: writing errors that include capital and italics. Word writing errors that include writing prepositions, chopping letters, and pronouns. Writing punctuation errors that include period punctuation and comma punctuation.